Comic Strip Media as An Innovative Media for Adab Learning - Sigit, Sigit Dwi Laksana; Arif, Zainal; Ariyanto, Ayok; Saputro, Anip Dwi (Journal of Educational Technology and Instruction, 2024)
One picture is worth a thousand words (one picture is worth a thousand words). This sentence is very well addressed in comic media. The existence of comics which is increasing rapidly must be the center of attention for educators, especially educators at the elementary school level, in this case, tertiary institutions. Scenes shown in comic books often display behavior that students should not emulate and sometimes parents and lecturers don't pay much attention. Problems like this if left unchecked can make the next generation of the nation have dishonorable behavior. Looking at these problems, the world of education began to look at the comic media. Comic media began to be developed in the world of education, actually comics in the world of education is not a new thing, a psychologist who is well-known for behavioristic theory Edward Lee Thorndike has conducted research on comics that students who read more comics for example in a month at least one comic book, then it's the same as reading textbooks every year, this has an impact on students' reading abilities and vocabulary mastery far more than students who don't like comics. Comic strip media is different from existing comics in that the storylines in comics are made as attractive as possible by raising themes or subject matter in elementary schools. The existence of Media Comic Strip media is expected to be an innovative media that can be used as an alternative media to overcome students who have learning difficulties, especially in terms of interest and understanding of the material